2022
DOI: 10.1007/s00392-022-02091-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-field ablation-based pulmonary vein isolation: acute safety, efficacy and short-term follow-up in a multi-center real world scenario

Abstract: Purpose Pulsed-field ablation (PFA) is a new energy source to achieve pulmonary vein isolation (PVI) by targeted electroporation of cardiomyocytes. Experimental and controlled clinical trial data suggest good efficacy of PFA-based PVI. We aimed to assess efficacy, safety and follow-up of PFA-based PVI in an early adopter routine care setting. Methods Consecutive patients with symptomatic paroxysmal or persistent atrial fibrillation (AF) underwent PVI using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
(37 reference statements)
2
32
0
Order By: Relevance
“… 7 This is the first prospective large-scale study to show a very low-risk profile of pulsed field ablation, even within a 41-center setting with multiple operators; other pulsed field ablation studies with >100 patients have reported major complication rates, from 1.5% to 3.3%, or low rates within single-center studies. 21 24 In this study, the total risk of primary safety adverse events was <1%, with no indication of pulmonary vein, esophageal, or phrenic damage. Furthermore, silent cerebral risk was in keeping with other forms of ablation, which have reported rates of 4% to 10% for cryoablation and 0% to 19% for radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“… 7 This is the first prospective large-scale study to show a very low-risk profile of pulsed field ablation, even within a 41-center setting with multiple operators; other pulsed field ablation studies with >100 patients have reported major complication rates, from 1.5% to 3.3%, or low rates within single-center studies. 21 24 In this study, the total risk of primary safety adverse events was <1%, with no indication of pulmonary vein, esophageal, or phrenic damage. Furthermore, silent cerebral risk was in keeping with other forms of ablation, which have reported rates of 4% to 10% for cryoablation and 0% to 19% for radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 61%
“…Some studies suggested better efficacy with pulsed field ablation, but these were pilot studies with surrogate outcomes or limited-center studies without robust arrhythmia monitoring. 21 , 23 , 24 , 32 , 33 One large pulsed field ablation registry showed lower success compared with early pilot data. 22 , 23 , 32 , 33 Only 1 pulsed field ablation study has published results with robust arrhythmia monitoring such as weekly transtelephonic transmissions, but 20% of the published 121-patient cohort did not reach 12-month follow-up, and 32% underwent a repeat ablation at any time during the study.…”
Section: Discussionmentioning
confidence: 99%
“…2 Initial clinical observations in controlled trials recently reported data on safety, efficacy, and follow-up data of PFA-based PVI. 3,4 On the other hand, the RFB is a compliant balloon catheter compatible with a 3D electroanatomical mapping system (CARTO 3; Biosense Webster) and provides an established energy source; it allows for selective titration of RF energy delivery from each surface electrode to prevent collateral damage and to apply energy in a segmental area if needed. 5 Two multicenter trials (RADIANCE 5,6 and SHINE 7 ) demonstrated the feasibility, safety, and 12-month outcome of this technology.…”
Section: Discussionmentioning
confidence: 99%
“… 27) Other clinical studies reported similar data all highlighting the acute efficiency, short procedure time, beneficial safety profile and favorable rate of clinical outcomes up to 1 year follow-up. 88) 90) 91) …”
Section: Pulsed Field Ablation: Efficacy Safety and Fields Of Applica...mentioning
confidence: 99%